Broadband Economics Lessons from Japan - Ida, Takanori (Taylor & Francis, 2019)
Japan's high-speed Internet access services such as ADSL, CATV Internet and FTTH are considered the cheapest and fastest state-of-the-art services drawing international attention. In this book the author introduces the current status of broadband services in Japan and their recent development in competition policy. An econometric model is proposed and discussed to analyse access demand. The purpose of the analysis is to understand quantitively the current status of the rapidly developing Japanese broadband services while providing an academic and practical basis for conceiving prospective competition policies. The book is composed of three parts. The first part introduces the diffusion of current Broadband services, the economics of network industries and related econometric model analysis. The second part elucidates in detail the development of fixed-line broadband services, IP phone services as well as mobile phone services. The third part consequently investigates the migration among broadband services, the fixed and mobile convergence and the digital divide problem.